Manajemen Perilaku Organisasi dalam Mewujudkan Sumber Daya Manusia yang Kompeten di SD Negeri Lamper Kidul 01 - Karima, Ida; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This research describes organizational behavior management in creating competent human resources at SD Negeri Lamper Kidul 01. This research is a qualitative descriptive research. The results of data analysis show that organizational behavior management in creating competent human resources at SD Negeri Lamper Kidul 01 Semarang is efficient and effective. Research objectives 1) describe the management of organizational behavior at SD Negeri Lamper Kidul 01 Semarang in realizing human resources. 2) Analyze the obstacles and solutions in this research. The results of the research reveal regarding (1) Management of Madrasah Organizational Behavior at SD Negeri Lamper Kidul 01 Semarang in realizing human resources which is carried out by planning; carried out by analyzing all activities or workload, intellectual capacity, capability, work experience and example. Recruitment; prioritize academic, non-academic achievements, good morals, and put aside kinship relationships and prioritize achievement and professionalism. Development; changing behavior so that changes and improvements occur through workshops, education and training. Supervision; carried out according to the schedule once a month for the entire series of school activities, student conditions, infrastructure, teachers, programs, facilities. Evaluation; three stages, namely monthly, mid-semester and end of semester, and the end of the learning year. Obstacle; The teaching staff does not match what is needed, they are not graduates of teacher education, teachers who already teach are not in their field, there is minimal supervision, minimal capacity development, and lack of evaluation. Solution; recruitment management with academic and non-academic selection, teacher training development, workshops, supervision and attention to the organization.